Perancangan Sistem Absensi Guru Berbasis Web Di Smk Kesuma Bangsa 1 Depok - Alfian Pratama Putra; Muhammad Ari Wirayudha; Rinaldy Abdul Muthalib; Wasis Haryono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This Kesuma Bangsa 1 Depok Vocational High School means an education forum that already has a fairly large number of teachers. Therefore, the Kesuma Bangsa 1 Depok Vocational High School always tries to provide the best possible service in accordance with the demands of the development of the current technological system which is growing so fast. with a fairly large number of teachers, and the absence of teachers still using a manual system or not yet computerized which greatly causes errors in absenteeism, monthly absentee data recap, because the data stored for teachers does not use a database, but only in the form of sheets of paper. This institution has 25 permanent teachers and 4 honorary teachers. Therefore, the use of a computerized system needs to be used to assist the process of teacher attendance data collection activities to prevent errors that often occur in data collection. Utilization of personal computer technology using web and PHP programming languages which are very helpful in forming the system, in order to launch the attendance system so that it can run effectively in terms of use and efficiency in all use of devices and energy.